Severe hospital events following symptomatic infection with Sars-CoV-2 Omicron and Delta variants in France, December 2021–January 2022: A retrospective, population-based, matched cohort study. (June 2022) - Auvigne, Vincent; Vaux, Sophie; Strat, Yann Le; Schaeffer, Justine; Fournier, Lucie; Tamandjou, Cynthia; Montagnat, Charline; Coignard, Bruno; Levy-Bruhl, Daniel; Parent du Châtelet, Isabelle
Summary: Background: A rapid increase in incidence of the SARS-CoV-2 Omicron variant (sub-lineage BA.1) occurred in France in December 2021, while the Delta variant was prevailing since July 2021. We aimed to determine whether the risk of a severe hospital event following symptomatic SARS-CoV-2 infection differs for Omicron versus Delta. Methods: We conducted a retrospective cohort study to compare severe hospital events (admission to intensive care unit or death) between Omicron and Delta symptomatic cases matched according to week of virological diagnosis and age. The analysis was adjusted for age, sex, vaccination status, presence of comorbidities and region of residence, using Cox proportional hazards model. Findings: Between 06/12/2021–28/01/2022, 184 364 cases were included, of which 931 had a severe hospital event (822 Delta, 109 Omicron). The risk of severe event was lower among Omicron versus Delta cases; the difference in severity between the two variants decreased with age (adjusted Hazard Ratio (aHR)=0·13 95%CI: 0·08–0·20 among 40–64 years, aHR=0·50 95%CI: 0·26–0.98 among 80+ years). The risk of severe event increased with the presence of comorbidities (for very-high-risk comorbidity, aHR=4·15 95%CI: 2·86–6·01 among 40–64 years) and in males (aHR=2·28 95%CI: 1·82–2·85among 40–64 years) and was higher in unvaccinated compared to primo-vaccinated (aHR=7·29 95%CI: 5·58–9·54 among 40–64 years). A booster dose reduced the risk of severe hospital event in 80+ years infected with Omicron (aHR=0·29; 95%CI: 0·12–0·69). Interpretation: This study confirms the lower severity of Omicron compared to Delta. However, the difference in disease severity is less marked in the elderly. Further studies are needed to better understand the interactions between age and severity of variants. Funding: The study was performed as part of routine work at Public Health France.